2022
DOI: 10.1590/fst.97521
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of antibacterial sodium dehydroacetate/modified film

Abstract: Antibacterial polyethylene (PE) packaging films were prepared by combining granulation and casting with antibacterial agents sodium dehydroacetate (SD) and potassium sorbate (PS). The scanning electron microscopy (SEM) was used to characterize the structure of the films, and the effects of various additives on their physical, optical, microstructure, thermal stability, and antibacterial properties were investigated. The results show that when the SD: PS ratio is 2:1, the antibacterial film has higher tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Gelatin is an important natural biomolecular material; due to its strong film-forming ability, good transparency and oxygen resistance, excellent renewable performance, good biodegradability, and low cost, it has a wide range of applications in food, pharmaceutical, chemical, and other fields. Studies have shown that natural antioxidant substances such as potassium sorbate and natural antimicrobial substances such as chitosan can be added to gelatin to prepare a gelatin film with antioxidant or antimicrobial effects; this can be wrapped on the surface of cold, fresh meat to reduce drip loss, improve color change, and extend shelf life [13,14]. Wu et al [15] prepared a fish gelatin antibacterial composite film using cinnamaldehyde and its sulfobutyl ether-β-cyclodextrin complex, which effectively inhibited the growth of microorganisms in grass carp slices.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin is an important natural biomolecular material; due to its strong film-forming ability, good transparency and oxygen resistance, excellent renewable performance, good biodegradability, and low cost, it has a wide range of applications in food, pharmaceutical, chemical, and other fields. Studies have shown that natural antioxidant substances such as potassium sorbate and natural antimicrobial substances such as chitosan can be added to gelatin to prepare a gelatin film with antioxidant or antimicrobial effects; this can be wrapped on the surface of cold, fresh meat to reduce drip loss, improve color change, and extend shelf life [13,14]. Wu et al [15] prepared a fish gelatin antibacterial composite film using cinnamaldehyde and its sulfobutyl ether-β-cyclodextrin complex, which effectively inhibited the growth of microorganisms in grass carp slices.…”
Section: Introductionmentioning
confidence: 99%